HUBUNGAN KADAR TIMBAL (Pb) DENGAN KADAR MALONDIALDEHID (MDA) DALAM DARAH PADA IBU HAMIL DI WILAYAH PANTAI KABUPATEN BREBES - Hari Ismanto; Suhartono Suhartono; Yusniar Hanani Darundiati; Nurjazuli Nurjazuli (Jurnal Kesehatan Masyarakat (Undip), 2019)
The highest maternal mortality in Central Java was found in Brebes District with 54 cases in 2016 and 52 cases in 2015. Lead exposure may contribute to the causes. The study was conducted in four coastal areas of sub-districts in Brebes. The purpose of this study was to determine the relationship between lead (Pb) levels with malondialdehyde (MDA) levels of pregnant women’s blood, it was an observational analytic research with a cross sectional study design. The samples were 85 pregnant women. Data were analyzed descriptively by univariate analysis, data on lead levels and malondialdehyde levels were analyzed using Rank Spearman correlation test. The study showed that the average age of pregnant women was 30.15 years old with the largest age category being 20-35 years. The average gestational age was 27.62 weeks or predominantly in the second and third trimesters of pregnancy (43.5% and 54.1%). The pregnant women in the study area had high risk of lead exposure sourced from cigarette and pesticides (28.2% and 78.8%). The average lead level in the blood of pregnant women is 42.67 µg / dl, while malondialdehyde was 377.3 ng/ml. The results of the correlation test of lead levels with malondialdehyde levels in the blood of pregnant women showed that both variables were not related (p Value>0.05). It is important to highlight the lead levels of blood in the study area. Pregnant women are advised to prevent lead exposure by avoiding cigarette smoke, pesticides, not consuming lead contaminated seafood, and minimizing the vehicle emission exposure.